2015 International Conference on Robotics, Automation, Control and Embedded Systems (RACE) 2015
DOI: 10.1109/race.2015.7097247
|View full text |Cite
|
Sign up to set email alerts
|

EEG based emotion recognition system using MFDFA as feature extractor

Abstract: Emotion is a complex set of interactions among subjective and objective factors governed by neural/hormonal systems resulting in the arousal of feelings and generate cognitive processes, activate physiological changes such as behavior. Emotion recognition can be correctly done by EEG signals. Electroencephalogram (EEG) is the direct reflection of the activities of hundreds and millions of neurons residing within the brain. Different emotion states create distinct EEG signals in different brain regions. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Murugappan et al ( 2010 ) used the “db4” wavelet function for deriving a set of conventional and modified energy-based features from EEG signals for classifying emotions. Paul et al ( 2015 ) used the multifractral detrended fluctuation analysis (MFDFA) method to extract features and used a support vector machine (SVM) to categorize the EEG feature space related to various emotional states into their respective classes. Jiang et al ( 2020a ) used transfer learning to reduce the differences in data distribution between the training and testing data (Yang et al, 2016 ; Jiang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Murugappan et al ( 2010 ) used the “db4” wavelet function for deriving a set of conventional and modified energy-based features from EEG signals for classifying emotions. Paul et al ( 2015 ) used the multifractral detrended fluctuation analysis (MFDFA) method to extract features and used a support vector machine (SVM) to categorize the EEG feature space related to various emotional states into their respective classes. Jiang et al ( 2020a ) used transfer learning to reduce the differences in data distribution between the training and testing data (Yang et al, 2016 ; Jiang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain activity patterns acquired through fNIRS, fMRI, EEG, or electrocorticography (ECoG) are decoded into an input signal to manipulate external devices such as cursors [16], [17], [18], wheelchairs [19], [20] or exoskeletons [21], [22], [23]. BCI have also been used to detect physiological states such as attention [24], drowsiness [25], [26] and various emotions [27], [28], [29]. To date, the three main techniques to acquire an interpretable signal for BCI are steady-state visually evoked potential (SSVEP), P300 oddball stimulus, and MI somatosensory rhythms.…”
Section: Introductionmentioning
confidence: 99%
“…Other than stimuli, there are certain important issues such as display setup, participant's information and ambient conditions need to be considered in stimuli presentation and reported accordingly. Nevertheless, few studies have not revealed these important factors like, laboratory environment [73], [74], [78] (screen size, ambient conditions, etc.) and the participant information [32], [132]…”
Section: Review Workmentioning
confidence: 99%